(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is a critical investigation of the Zimbabwean Tsonga rain petitioning ritual namely nkelekele, with critical insights on how it manifests scholarly levels of Indigenous Knowledge Systems. Among the Tsonga, it is believed that the rubbish on the environment can result in the absence of rain. In this ritual, the participants clean up the environment and burn the rubbish at the dumping place. The findings revealed that, there are various forms of indigenous knowledge systems in this rainmaking ritual which include cloud formation, cleaning the environment, preventing outbreak of diseases, avoiding the spread of veld fires, protecting children’s health as well as livestock rearing. The basic, initial purpose of nkelekele was to ask rain from the ancestors. However, it has been observed that there are critical lessons and observations that can be drawn from the ritual in light of a people’s unrecorded indigenous knowledge system agenda.